Anemia in disadvantaged children aged under five years; quality of care in primary practice - Casey Mitchinson; Natalie Strobel; Daniel McAullay; Kimberley McAuley; Ross Bailie; Karen M. Edmond (BMC, 2019)
Abstract Background Anemia rates are over 60% in disadvantaged children yet there is little information about the quality of anemia care for disadvantaged children. Methods Our primary objective was to assess the burden and quality of anemia care for disadvantaged children and to determine how this varied by age and geographic location. We implemented a cross-sectional study using clinical audit data from 2287 Indigenous children aged 6-59 months attending 109 primary health care centers between 2012 and 2014. Data were analysed using multivariable regression models. Results Children aged 6-11 months (164, 41.9%) were less likely to receive anemia care than children aged 12-59 months (963, 56.5%) (adjusted odds ratio [aOR] 0.48, CI 0.35, 0.65). Proportion of children receiving anemia care ranged from 10.2% (92) (advice about 'food security') to 72.8% (728) (nutrition advice). 70.2% of children had a hemoglobin measurement in the last 12 months. Non-remote area families (115, 38.2) were less likely to receive anemia care compared to remote families (1012, 56.4%) (aOR 0.34, CI 0.15, 0.74). 57% (111) aged 6-11 months were diagnosed with anemia compared to 42.8% (163) aged 12-23 months and 22.4% (201) aged 24-59 months. 49% (48.5%, 219) of children with anemia received follow up. Conclusions The burden of anemia and quality of care for disadvantaged Indigenous children was concerning across all remote and urban locations assessed in this study. Improved services are needed for children aged 6-11 months, who are particularly at risk.